Analysis of Revenue Sources and Alternatives at Minaret College, Australia 2023–2024 - Yuliati, Yuliati; Afif, Muslihul; Munadi, Muhammad (Universitas Negeri Semarang, 2025)
This article aims to analyze the structure and development of Minaret College’s revenue in Australia, with a focus on the 2023–2024 financial report. The research method employs a qualitative approach using the 2023–2024 financial report text. Data analysis utilizes quantitative percentage analysis and qualitative descriptive interpretation. The results show that the institution’s income is predominantly derived from government grants (federal and state), accounting for more than 85% of total revenue. In 2024, total income increased by 6.49%, with the main contributions coming from federal government grants (65.23%) and state grants (19.77%). Other income sources, including parental contributions and paid program revenues, exhibited slower growth but remain essential for financial diversification strategies. This article highlights the institution’s need to develop more sustainable alternative income sources, such as endowment funds, paid programs, and community-based philanthropy. Financial management is conducted transparently through publication on the institution’s website and the ACNC (The Australian Charities and Not-for-profits Commission). To enhance trust and partnership opportunities, the institution is audited by the independent auditor Bunnet & Bassal Pty Ltd. This study offers strategic policy recommendations to improve the financial independence of Minaret College and ensure its operational sustainability in the context of evolving global education policies.